Baloxavir Marboxil 2% Granules in Japanese Children With Influenza: An Open-label Phase 3 Study. Issue 8 (August 2020) - Yokoyama, Takato; Sakaguchi, Hiroki; Ishibashi, Toru; Shishido, Takao; Piedra, Pedro A.; Sato, Chisako; Tsuchiya, Kenji; Uehara, Takeki
Abstract : Background: A granule formulation of baloxavir marboxil, a selective inhibitor of influenza cap-dependent endonuclease, was newly developed for children with difficulty swallowing tablets. Methods: A multicenter open-label study was conducted during the 2017–2018 influenza season to assess the safety, pharmacokinetics and clinical/virologic outcomes of single, oral, weight-based doses of baloxavir granules in Japanese children infected with influenza virus. The primary clinical endpoint was the time to illness alleviation of influenza. Results: All 33 enrolled children completed the study and received baloxavir (1 mg/kg for 12 children weighing <10 kg, 10 mg for 21 children weighing 10 to <20 kg). Detected viruses were influenza B (36.4%), A(H1N1)pdm09 (33.3%) and A(H3N2) (27.3%). Adverse events (AEs) were reported in 54.5% of children. No deaths, serious AEs or AEs leading to discontinuation were reported. The mean (SD) plasma concentrations of baloxavir acid at 24 hours post-dose were 72.8 (24.0) and 51.3 (19.3) ng/mL in the 1-mg/kg and 10-mg dose groups, respectively. The median time to illness alleviation (95% confidence interval) was 45.3 (28.5–64.1) hours. A >4-log decrease in infectious viral titer occurred on day 2 and a temporary 2-log increase on day 4. Polymerase acidic protein/I38T/M-substituted viruses were detected in 5 children infected with influenza A, but none with influenza B. Conclusions: Baloxavir granules and the weight-based dose regimen were considered to be well tolerated in children, with rapid influenza virus reduction and associated symptom alleviation. Evidence of baloxavir activity against influenza B was observed, but further data are required for confirmation. Abstract : Supplemental Digital Content is available in the text.